(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article presents the comparative analysis of the popular theory of “web society” by Manuel Castells and postmodern theory. Castells himself related negatively to postmodernism but his analysis of contemporary society is quite postmodernistic. There considered such questions of contemporary culture as urbanism, informatisation, consumerism, lifestyle, yuppies and others. Postmodernist theory and methodology let better understand ongoing changes in society and culture.